Effects of crumb rubber aggregate on the static and fatigue performance of reinforced concrete slabs. (15th November 2019) - Xie, Jianhe; Zheng, Yuwen; Guo, Yongchang; Ou, Rongxuan; Xie, Zhihong; Huang, Liang
Abstract: The utilization of crumb rubber concrete (CRC) is a sustainable solution for dealing with waste tyres. The aim of this work is to investigate the effects of rubber instead of fine aggregates on the static and fatigue performance of reinforced concrete slabs. Based on a series of experiments conducted to determine the material properties of rubberized concrete, a total of eight one-way reinforced concrete slabs were cast, including six CRC slabs and two normal slabs as control specimens according to rubber content and load type, and then were tested under four-point bending loads. The deflection, concrete strain, steel strain and load-bearing capacity of the reinforced CRC slab with different rubber content under monotonic loading were firstly investigated. And then, the effect of rubber incorporation on the failure behavior of reinforced concrete slab was examined, including the fatigue damage evolution, failure mode and fatigue life. The results indicate that rubberized concrete with appropriate mix proportions has the potential to be used in structural members. However, a high rubber content may result in the over-reinforcement of the RC slab, and could be also detrimental to its fatigue life. High fatigue stress can degrade the bonding between the rubber and paste, suggesting that the advantages of rubber that facilitate energy absorption cannot be utilized. For the safe design of rubber as a replacement for fine aggregates, the content of rubber in RC slab is suggested to be no more than 10%.